Keteladanan Guru dalam Menanamkan Kedisiplinan Siswa Sekolah Dasar melalui Pembelajaran Daring - Febrianty, Dwi; Cendana, Wiputra (Musamus Journal of Primary Education, 2021)
Discipline is manifested in the student's compliance with the applicable class rules procedures in the classroom. The authors found problems related to the discipline of elementary school students. The discipline of grade 3 elementary school students does not show any indicators of discipline such as not following the rules procedures applicable in online learning. The purpose of writing this research is to review and describe the teacher's accuracy in instilling the discipline of elementary school students through online learning. The author uses research method with descriptive qualitative. Self-control of teachers is also an example that students certainly imitate. Based on the results of analysis and the findings of previous research, researchers concluded that the picture of discipline in grade 3 elementary school should be shown by compliance, obedience, self-control of the rules and procedures applicable in online learning. Discipline aims to bring students to maturity and change. The author recommends that elementary school teachers apply strictness to improve the discipline of elementary school students owned by students. Although the accuracy provided online learning can have a positive impact on student discipline in online learning. Students are expected to get used to discipline and exemplify teachers in terms of discipline.